1978
DOI: 10.1002/ijc.2910210120
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hamster cells transformed by the combined action of chemical and virus

Abstract: Pretreatment of hamster cells with chemical carcinogen enhances transformation by a simian adenovirus, SA7. Such transformants were compared to cells transformed by SA7 alone for the presence of virus-specified antigens, and for the ability to clone in soft agar and to form progressively growing sarcomas in hamsters. The SA7 "T" antigen content and the relative cloning efficiencies in agar of cell lines of both groups were similar. Some cell lines obtained by pretreatment with chemical carcinogen, however, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
2
3
1
Order By: Relevance
“…Comparable results have been obtained in studies employing hamster embryo cells treated with MMS and then infected with SA7 [28,29]. MMS pretreatment did result, however, in an increase in the quantities of SA7 DNA in the total population of hamster embryo cells 2-9 d after MMS treatment and viral infection 1291.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Comparable results have been obtained in studies employing hamster embryo cells treated with MMS and then infected with SA7 [28,29]. MMS pretreatment did result, however, in an increase in the quantities of SA7 DNA in the total population of hamster embryo cells 2-9 d after MMS treatment and viral infection 1291.…”
Section: Discussionsupporting
confidence: 73%
“…In the case of the alkylating carcinogen, MMS enhancement of viral transformation of CREF cells was not associated with an alteration in either the biological or biochemical properties of transformants nor was enhancement associated with a change in the quantity of integrated H5hrltransforming genes (E 1 A or E l B) or the integration of viral DNA in similar DNA sites [9,12]. Comparable results have been obtained in studies employing hamster embryo cells treated with MMS and then infected with SA7 [28,29]. MMS pretreatment did result, however, in an increase in the quantities of SA7 DNA in the total population of hamster embryo cells 2-9 d after MMS treatment and viral infection 1291.…”
Section: Discussionmentioning
confidence: 96%
“…Chemical carcinogens given prior to subsequent RLV infection of rat embryo cells were ineffective. Conversely, pretreatment by chemical carcinogens has been reported to enhance adenovirus transformation of hamster embryo cells in vitro (5,9). In our in vivo system, a 5-hr pretreatment with MMS in relation to FLV injection enhanced leukemogenesis, but posttreatment did not.…”
Section: Effect Of Mms On Virus-resistant Biosjfi Hybrid Micecontrasting
confidence: 59%
“…Ball and McCarter (3) and Igel et al (4) subsequently demonstrated reproducible activation and production of leukemia virus after treatment with chemical carcinogens. These findings have been confirmed in a number of in vivo and in vitro studies suggesting that interaction with exogenous (5)(6)(7)(8)(9)(10)(11)(12) or endogenous (13)(14)(15)(16) viruses may play an important role in the production of some tumors by chemical carcinogens (also see 17 for review). More recently, Pottathil ef al.…”
supporting
confidence: 58%
See 1 more Smart Citation